PENGARUH TENAGA KERJA, PEMBIAYAAN BANK SYARIAH, EKSPOR DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI SEKTOR PERTANIAN DI INDONESIA PERIODE 2017-2021 - Amanda, Resti; Lutfi, Mohammad (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2022)
The high employment opportunities in the agricultural sector have the potential to increase economic growth in the agricultural sector. However, various factors have not been optimized, such as the workforce itself, the distribution of Islamic bank financing which is still low, commodity exports are still small, and fluctuations in the inflation rate. This study was conducted to analyze the relationship between the variables of labor, Islamic bank financing, exports and inflation partially and simultaneously on the economic growth of the agricultural sector in Indonesia. Data analysis uses panel data regression with the help of Eviews 12 in 27 Indonesian provinces for the period 2017-2021 period. The results showed that partially labor, Islamic bank financing and exports had no significant effect on the economic growth of the agricultural sector. Inflation partially positive and significant effect on economic growth in the agricultural sector. Meanwhile, simultaneously, labor, Islamic bank financing, exports and inflation have a significant effect on the economic growth of the agricultural sector in Indonesia for.